Contemporary early results of late repair of tetralogy of Fallot in children: a single-centre case series (Swiss Medical Weekly, 2021)
AIMS To describe the early results of complete repair of tetralogy of Fallot (TOF) in children older than one year of age. METHODS We identified all patients older than one year of age who underwent TOF repair between 2007 and 2017. Data collected included type of surgical repair, survival at 30 days after surgery, reintervention within 30 days of surgery, length of stay in the intensive care unit (ICU), length of stay in hospital, and degree of residual right ventricular outflow tract (RVOT) stenosis and pulmonary insufficiency 30 days after surgery. RESULTS 125 children (median age 4.4 years, interquartile range [IQR] 3–5.7) underwent complete repair of TOF, with pulmonary valve preservation in 66%, a transannular patch in 19%, and a valved right ventricular-to-pulmonary artery conduit in 15%. All patients survived. There were twelve (9.6%) reinterventions. Median ICU length of stay was 7 days and median hospital length of stay was 12 days. Significant residual RVOT stenosis was present in 7.2% and significant pulmonary insufficiency in 19.2%. Patients with a transannular patch had a significantly higher proportion of significant residual RVOT stenosis and significant pulmonary insufficiency compared with the other types of surgical repair. CONCLUSIONS Compared with the existing literature on complete late repair of TOF in children, this study showed good early results with no mortality, similar rates of reintervention and valve-preserving surgery, higher ICU and hospital length of stay, higher incidence of significant residual RVOT stenosis, and lower incidence of significant pulmonary insufficiency. Repair with a transannular patch was a risk factor for significant residual RVOT stenosis and significant pulmonary insufficiency.